1999
DOI: 10.1143/jjap.38.l113
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Emission from Zinc Oxide giving an Electron Spin Resonance Signal at g=1.96

Abstract: ZnO polycrystals doped with Li, Cu or Al were prepared by solid-state reactions and their cathodoluminescence (CL) and electron spin resonance (ESR) spectra were measured. A strong yellow emission centered at 2.0 eV was observed for the Al-doped specimen and its intensity was higher than that of the green emission observed for the Al-free samples. The intensity of the green emission was independent of the annealing atmosphere. On the other hand, the intensity of the yellow emission was enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…30 A yellow emission band was detected in pulsed laser deposited ZnO 31 and in ZnO:Al prepared by solid-state reactions. 32 A red emission band was detected in spray pyrolysis deposited ZnO 33 and in ZnO singlecrystals implanted, at 475°C, with Li, Na, N, P and Ne ions. 34 These emissions are mainly due to native (or intrinsic) defects, including vacancies, interstitials and anti-sites.…”
Section: Introductionmentioning
confidence: 97%
“…30 A yellow emission band was detected in pulsed laser deposited ZnO 31 and in ZnO:Al prepared by solid-state reactions. 32 A red emission band was detected in spray pyrolysis deposited ZnO 33 and in ZnO singlecrystals implanted, at 475°C, with Li, Na, N, P and Ne ions. 34 These emissions are mainly due to native (or intrinsic) defects, including vacancies, interstitials and anti-sites.…”
Section: Introductionmentioning
confidence: 97%
“…For example, the EPR signal of g = 1.96 was attributed to oxygen vacancy, 10 but some others argued that the oxygen vacancy signal was at g = 1.99. 11 The green luminescence at about 2.4 eV was correlated with oxygen vacancy by many researchers, [12][13][14][15] but it was also attributed to other defects such as V Zn , 16,17 Zn i , 18,19 O Zn , 20,21 and even Cu impurities. 22 DLTS revealed a major defect level L2 at E c − 0.3 eV in the as-grown ZnO, but the assignment of this level is also rather difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Since these emissions are located in a wide range of visible spectrum, great efforts have been made to tailor these visible emissions. It is found that doping ZnO with Li [11][12][13] or Al [14] leads to the yellow luminescence. Other dopants, including Mg [15], W [16], V [16], Eu [17] and Er [18], have been also investigated.…”
Section: Introductionmentioning
confidence: 99%